Characteristic of feeding of mullet fishes in Shabolatsky estuary - Shekk, Pavel; Burgaz, Marina (ScienceRise: Biological Science, 2017)
The worsening of the ecological situation in the last years resulted in the decrease of biodiversity and general fish productivity of the saltish-water Shabolatsky estuary, placed in Danube-Dniester interfluves. It doesn’t allow to use it effectively for the traditional pasturable cultivation of mullet fish. The aim of the work was to study the features of feeding, food relations and growth of indigenous species of mullet (stripped mullet, leaping grey mullet, golden mullet) and soiuy mullet acclimater at the pasturable cultivation under conditions of Shabolatsky estuary. The collection of ichthyological material was realized in 2012-2014. At the study of mullet feeding were used standard methods that allowed to assess season changes of qualitative and quantitative parameters of feeding and food relations of mullet: stripped mullet - Mugil cephalus, golden mullet – Liza aurata, leaping grey mullet – Liza saliens, soiuy mullet – Liza haematocheilus. For the first time there was given the qualitative characteristics of feeding and food relations of different types of mullet in season and age aspects. It was demonstrated, that leaping grey mullet and golden mullet of all age groups in all seasons of a year prefer animal food; stripped mullet and soiuy mullet – detritus and vegetable food. The most similarity was inherent to the qualitative compositions of rations of yearlings of all mullet species in the spring period (feeding similarity index FSI – 63,0-76,5). In summer the food composition changed (decreased for animal plankton and increased for zoobenthos). The tension of food relations decreased (FSI – 49,8-75,0). In autumn the most similarity of the food character was typical for second-year golden mullet and leaping grey mullet on the one side and second-year and third-year stripped mullet and soiuy mullet (up to 75-89% of detritus and vegetable food) on the other one. At the same time golden mullet and leaping grey mullet essentially differed from stripped mullet and soiuy mullet by the food character. The decrease of zooplankton and zoobenthos production, noticed in Shabolatsky estuary in last years resulted in the decrease of the growth speed of leaping grey mullet and golden mullet. At the same time essential reserves of detritus of vegetable food provide the intensive growth of striped mullet and soiuy mullet. In the existent situation it is expedient to use striped mullet and soiuy mullet detritophages as main objects of the pasturable mullet cultivation to provide the maximal fish productivity of the water body.